European standards for quality assurance in vocational education and training and their implementation at the national level - Gruber, Thomai Svenja [Verfasser]; Sabbagh, Helena [Verfasser] (My University, 2013)
Comparability, transparency and mobility - this triad stands for one decade of extensive developments that were launched as part of the systematic efforts towards establishing a European education area. The establishment of a European quality assurance reference framework for initial and continuing vocational education and training is an important milestone in this process. The article enumerates the goals of the European process of quality assurance in vocational education and shows what relevance the European standards developed have for quality assurance in the German context. It also refers to the opportunities now open to Germany for having a say in the European discourse. The role of the German Reference Point for Quality Assurance in Vocational Education and Training is dealt with against that background. (BIBB-Doku)
Keywords: L 6.2 Qualitätsmanagement/Qualitätssicherung; S 2.2.5 Standards in der beruflichen Bildung; I 2.2 Europa; Berufsbildung; Qualitätssicherung; Bildungsstandards; EQAVET; Europa